Displacement and Diasporic Identity in Aesop’s The Town Mouse and the Country Mouse - Chachou, Ali Abdullah; Diniagama, Naseem (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
A fable has always been considered as a story for children. It is not only easy to read, but also has a moral story inside of it. However, some fable have a deeper meaning inside of it because fable is a fantasy invented to reflect reality but not in a form of a true story. for example, Aesop’s fable of the Town Mouse and the Country Mouse which resembles the condition of the diasporic issue in real, humanity lives, which is displacement. Displacement is a term for those who contend with the place they truly belong, whether it is their homeland or home, and when one already put an anchor to home as the only place where they could truly enjoying life, then attempting to expand their view onto another world, the general problem they will felt out of place is either ruined expectation, the shifting gear of lifestyle, and the relationship revolving around the character. Displacement has always been a problem when you move to an entirely different place like what the Country Mouse has been trough in the story. This research is intended to educate individuals about diasporic difficulties, which can be challenging to address at times, and to assist those who experience displacement in their daily lives.